Virginio Colombo : persistencia, arte, oficio - Fratarelli, Nicolás, 1961- (Personajes del siglo XX entre la arquitectura y el diseño (SCA) ;, 2021)
This book is the result of a meticulous study and recovery of files on the work of the Italian architect Virginio Colombo (1885-1927) by Nicolás Fratarelli. The passion, commitment and persistence in his research and teaching work, carried out in the field of the Faculty of Architecture, Design and Urbanism of the UBA, is evidenced in his author. Colombo was born in Milan, where he studied architecture at the Brera Academy, and arrived in Argentina in 1906. In his few years of professional life, he developed a very important career, in which an indisputable coherence and quality is recognized, both in its architectural aspects as artistic. Stylistically, his work is part of the so-called "modernisms", Art Nouveau or "New Art", a European trend that acquired an important presence in our country from 1900. This architectural expression will try to overcome the styles derived from classicism and revivals historical through complex and non-unitary national manifestations, which will constitute the genesis of the nascent modern architecture. A contribution of enormous quality to the knowledge of one of the great Argentine architects of the 20th century.